Systematic Literature Review: Use of Comic Media in Mathematics Learning - Putri, Tiara Zakiah (JMEA : Journal of Mathematics Education and Application, 2024)
Learning mathematics does not only depend on what material is taught, but also depends on how the material resources are provided/delivered. The low interest in learning mathematics and the difficulty of understanding formulas means that many children are less interested in studying mathematics. The lack of innovative learning media provided by teachers, the use of cellphones for online games means that students rarely open their textbooks. Choosing the right learning media can be a factor in a teacher's success in carrying out learning activities. The use of comics as a mathematics learning medium is motivated by the low interest in reading and analytical thinking skills among students in Indonesia. One of the factors that can trigger enthusiasm for reading and thinking is designing comic media. Comic learning media is used to increase students' motivation to learn mathematics so that it can ultimately increase students' interest in reading and the level of analytical thinking in solving mathematics problems. This research aims to conduct a literature review related to the effectiveness of using comic media in mathematics learning. The research method used is SLR (Systematic Literature Review).The purpose of SLR is to analyze, find, review, and interpret previous research on the use of learning materials or media in mathematics learning. Data collection was carried out by documenting all articles that had similar research to this research. The journal articles used in this research were 10 national journal articles taken from the last seven years of research conducted by researchers obtained from Dimensions. Based on this research, it was found that comic media in mathematics learning really helps teachers to increase students' interest in reading and problem solving abilities so that it is useful in improving student’s analytical thinking abilities.